Thermophysical and rheological properties of sorbitol + ([mmim](MeO)2PO2) ionic liquid solutions: Solubility, density and viscosity. (1st August 2020) - Abbasi, Mohammad; Pazuki, Gholamreza; Raisi, Ahmadreza; Baghbanbashi, Mojhdeh
Highlights: Solubility of sorbitol in m m i m M e O 2 P O 2 ionic liquid was measured at various temperatures. Densities and viscosities of sorbitol +  m m i m M e O 2 P O 2 solutions were measured at various temperatures. The Flory-Huggins model was applied to predict solubility of sorbitol in m m i m M e O 2 P O 2 ionic liquid. The common equations were applied to correlate density and viscosity of solution. The flow curve showed that sorbitol-IL solution has Newtonian behaviour. Abstract: In this study, the solubility, density and viscosity of sorbitol as a sugar alcohol in the ([mmim](MeO)2 PO2 ) ionic liquid (IL) were measured. The results indicated that sorbitol is highly soluble in this IL. The Flory-Huggins model with an average value for the χ parameter was successfully applied to predict the solubility of sorbitol in IL. The thermodynamic properties such as enthalpy, entropy and Gibbs free energy of dissolution were obtained using experimental solubility data, which demonstrated that the dissolution process is endothermic and non-spontaneous and includes an entropy increase. In addition, the apparent molar volume, apparent molar expansion and thermal expansion coefficient were calculated. The study of the rheological behavior revealed that the sorbitol/IL solution is Newtonian and the Arrhenius, Litovitz, Orrick-Erbar-Type and Vogel-Fulcher-Tamman models were used to correlate the viscosity data.